Sharī‘ah Court-annexed ADR: The Need for Effective Dispute Management in Waqf, Hibah and Wasiyyah Cases in Malaysia - Oseni, Umar Aimhanosi (2012)

(untitled)
Being one of the most progressive Muslim countries in the 21st century, Malaysia has remained the cynosure of all eyes in the Muslim world. One of the major institutions in governance is the administration of justice system, which generally promotes access to justice as the last hope for the less privileged. To this end, this paper attempts to reconstruct the need to build on existing initiatives in the administration of justice mechanism of the Sharī‘ah judiciary in Malaysia with special reference to disputes involving waqf, hibah and wasiyyah issues. It is therefore argued that rather than waiting for emerging issues such as cases involving waqf survey to emerge before coming with up with sustainable mechanisms, which are fundamentally Sharī'ah-based, it is always more fitting to be proactive in a fast-growing economy such as Malaysia.